The relationship between learning strategies and learning interest against student learning outcomes at state elemetary - Zainar Zainar; Happy Fitria; Syaiful Eddy (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aims to analyze and describe : 1) the relationship between Learning Strategies and Student Learning Outcomes, 2) the relationship between Learning Interest and Student Learning Outcomes, 3) the relationship between Learning Strategies and Learning Interests on Student Learning Outcomes. The results stated: 1) there is a relationship between learning strategies and student learning outcomes; 2) there is a relationship between interest in learning and student learning outcomes; and 3) there is a relationship between learning strategies and interest in learning towards student learning outcomes.